Effect of biofilm coatings at metal-oxide/water interfaces II: Competitive sorption between Pb(II) and Zn(II) at Shewanella oneidensis/metal-oxide/water interfaces. (1st September 2016) - Wang, Yingge; Gélabert, Alexandre; Michel, F. Marc; Choi, Yongseong; Eng, Peter J.; Spormann, Alfred M.; Brown, Gordon E.
Abstract: Competitive sorption of Pb(II) and Zn(II) on Shewanella oneidensis MR-1 biofilm-coated single-crystal α-Al2 O3 (1 −1 0 2) and α-Fe2 O3 (0 0 0 1) surfaces was investigated using long-period X-ray standing wave-florescence yield (LP-XSW-FY) spectroscopy. In situ partitioning of aqueous Pb(II) and Zn(II) between the biofilms and underlying metal-oxide substrates was probed following exposure of these complex interfaces to equi-molar Pb and Zn solutions (0.01 M NaNO3 as background electrolyte, pH = 6.0, and 3-h equilibration time). At higher Pb and Zn concentrations (⩾10 −5  M), more than 99% of these ions partitioned into the biofilms at S. oneidensis /α-Al2 O3 (1 −1 0 2)/water interfaces, which is consistent with the partitioning behavior of both Pb(II) or Zn(II) in single-metal-ion experiments. Thus, no apparent competitive effects were found in this system at these relatively high metal-ion concentrations. However, at lower equi-molar concentrations (⩽10 −6  M), Pb(II) and Zn(II) partitioning in the same system changed significantly compared to the single-metal-ion systems. The presence of Zn(II) decreased Pb(II) partitioning onto α-Al2 O3 (1 −1 0 2) substantially (∼52% to ∼13% at 10 −7  M, and ∼23% to ∼5% at 10 −6  M), whereas the presence of Pb(II) caused more Zn(II) to partition onto α-Al2 O3 (1 −1 0 2) surfaces (∼15% to ∼28% at 10 −7  M, and ∼1% to ∼7% at 10 −6  M). The higher observed partitioning of Zn(II) (∼28%) at the α-Al2 O3 (1 −1 0 2) surfaces compared to Pb(II) (∼13%) in the mixed-metal-ion systems at the lowest concentration (10 −7  M) suggests that Zn(II) is slightly favored over Pb(II) for sorption sites on α-Al2 O3 (1 −1 0 2) surfaces under our experimental conditions. Competitive sorption of Pb(II) and Zn(II) at S. oneidensis /α-Fe2 O3 (0 0 0 1)/water interfaces at equi-molar metal-ion concentrations of ⩽10 −6  M showed that the presence of Pb(II) ions decreased Zn(II) partitioning onto α-Fe2 O3 (0 0 0 1) significantly (∼45% to <1% at 10 −7  M, and ∼41% to 3% at 10 −6  M), whereas adding Zn(II) caused only small changes in Pb(II) partitioning (∼59% to ∼47% at 10 −7  M, and ∼26% to ∼23% at 10 −6  M), suggesting that Pb(II) strongly outcompetes Zn(II) for sorption sites on S. oneidensis -coated α-Fe2 O3 (0 0 0 1) surfaces. Our study implies that caution should be taken when applying results obtained from partitioning studies of single-metal-ion systems to mixed-metal-ion systems at complex biofilm/mineral interfaces.